Perbandingan Kadar Arsen dalam Darah pada Perokok Aktif dan Pasif dengan Metode Inductively Coupled Plasma Mass Spectrometry (ICP - MS) - Meysa Nurviani Hasanah; M. Firman Solihat; Rohayati Rohayati; Mamat Rahmat (Akademi Analis Kesehatan Pekalongan, 2024)
Active smokers are people who smoke cigarettes directly, while passive smokers are people who do not inhale cigarettes directly, but inhale cigarette smoke emitted from people who are smoking. One of the toxic heavy metals found in cigarettes is arsenic. Tobacco is the main component of cigarettes that contain many chemicals, including arsenic. Arsenic can be found in tobacco due to several factors, namely soil characteristics, water, phosphate fertilizer, environmental factors, and types of pesticides. This study aims to determine the differences in blood arsenic levels in active and passive smokers using the Inductively Coupled Plasma - Mass Spectrometry (ICP - MS) method. The number of samples in this study was 30 samples; 15 blood samples of active smokers and 15 blood samples of passive smokers. The examination of arsenic levels was carried out at the West Java Provincial Health Laboratory. Based on the data, it was found that in the active smoker group, the average arsenic level was 0.53 μg/dL. While in passive smokers, the average arsenic level was 0.49 μg/dL. Then the Independent Sample T-Test test was conducted to determine the difference between the two groups of variables and the results were obtained p>0.05, based on these results there was no significant difference between arsenic levels in the blood of active smokers and passive smokers.